The Effect of Guerrilla Marketing on Purchasing Decisions: A Systematic Literature Review - Putri, Annisa Mawaddah Arief; Haeruddin, M. Ilham Wardhana; Hasdiansa, Ilma Wulansari; Musa, Muh. Ichwan; Abadi, Rahmat Riwayat; Mustafa, Muh. Yushar (Entrepreneurship, Management, and Business Research Journal, 2025)
In a company environment that is becoming more and more competitive, guerrilla marketing has become a potent and economical marketing tactic. The purpose of this study is to methodically examine how guerrilla marketing affects consumer choice. In this study, 7 pertinent prior papers were gathered, filtered, and analysed from a variety of academic sources using the systematic literature review (SLR) method. The analysis's findings demonstrate that guerrilla marketing has a major impact on consumer choices in a number of ways, such as through inventiveness, surprise, humour, message clarity, and emotional appeal. Additionally, this study reveals crucial mediators in the relationship between guerrilla marketing and purchase decisions, including brand image, innovation, and relevancy to the target demographic. The research's conclusions offer scholars and marketers important new information for comprehending guerrilla marketing's workings and creating more successful campaigns.